ANALYSIS OF THE DIGITALIZATION OF FINANCIAL RECORD-KEEPING AMONG MSMEs IN GONILAN VILLAGE - Rifadah Qoribah Salsabila; Rukmini Rukmini; Sri Laksmi Pardanawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to examine: (1) the implementation of digital financial record-keeping among MSMEs in Gonilan Village based on SAK EMKM; and (2) the challenges faced by MSMEs in Gonilan Village in implementing digital financial record-keeping. This study employed a descriptive qualitative research design. The subjects of the study were MSME actors in Gonilan Village who had used digital media to record their business finances. Data were collected through observation, interviews, and documentation. The data obtained were then analyzed through data reduction, data display, and conclusion drawing.The results of the study show that: (1) the implementation of digital financial record-keeping among MSMEs in Gonilan Village has been carried out through the use of digital media, such as Majoo, Spreadsheet, BukuKas, BukuWarung, and Bilas.id. However, based on SAK EMKM, its implementation is not yet fully complete. The income statement component is the most strongly implemented, while the statement of financial position has only been partially implemented, and the notes to the financial statements remain the weakest component; and (2) the challenges faced by MSMEs include limited understanding of basic accounting, uneven digital literacy, limited time, simple record-keeping habits, and the suboptimal use of financial information for business decision-making. Keywords: Digital Financial Record-Keeping, MSMEs, SAK EMKM.